The Influence of Emotion Regulation Strategies and Negative Cognitive Processing Bias on the Anxiety of College Students during the COVID-19 Epidemic - Qingbin Chen, Suhong Wu, Yin Lu (Design Engineering, 2020)
Objective: To explore the relationship between college students’ emotion regulation, negative cognitive processing bias and anxiety during the COVID-19 epidemic. Method: The NCPBQ, the ERQ and the anxiety factor subscale of the SCL-90 were used to conduct an online survey of 660 college students who live and study at home. Results: (1) The high anxiety group was significantly higher than the low group in terms of negative cognitive processing bias and expression inhibition scores (p<0.001), and significantly lower than the low group in terms of cognitive reassessment score (p>0.05). (2) Cognitive reassessment and expression inhibition can effectively predict the anxiety of college students with an explanation rate of 6.7%. (3) The negative contemplation bias, negative memory bias and negative interpretation bias can effectively predict the anxiety of college students with an explanation rate of 43.9%. (4) Negative memory bias, negative contemplation bias and negative interpretation bias play a mediating role in the influence of expression inhibition on anxiety. Conclusion: The emotion regulation strategies and negative cognitive processing bias of college students who study and live at home during the epidemic are closely related to their anxiety. It can reduce cognitive processing bias towards negative information, increase cognitive reassessment, and reduce expression inhibition to maintain and improve the mental health of college students.